2009
DOI: 10.1136/bjsm.2009.057885
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in endurance-trained athletes: Table 1

Abstract: Suggested management of AF in athletes should follow similar principles to those used to manage AF in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 37 publications
2
33
0
4
Order By: Relevance
“…However, the debate is of great relevance to the individual athlete who has profound myocardial remodeling or arrhythmias and needs us to understand the mechanism so that we can target our treatments and best prevent adverse outcomes. At present there is insufficient evidence to treat athletes with arrhythmias any differently from the general population, 80 but if we start to accept that exercise may contribute to the disease substrate then it would seem relevant to assess whether changes in exercise practice may change clinical outcomes. We need open-minded investigators with the patience, will, and resources to conduct adequately powered prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the debate is of great relevance to the individual athlete who has profound myocardial remodeling or arrhythmias and needs us to understand the mechanism so that we can target our treatments and best prevent adverse outcomes. At present there is insufficient evidence to treat athletes with arrhythmias any differently from the general population, 80 but if we start to accept that exercise may contribute to the disease substrate then it would seem relevant to assess whether changes in exercise practice may change clinical outcomes. We need open-minded investigators with the patience, will, and resources to conduct adequately powered prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Likely reasons include changes in autonomic drive including increased parasympathetic modulation at rest and increased sympathetic modulation during exercise, increased atrial size and increased inflammation (Sorokin et al 2009). …”
Section: Potential Arrhythmic Substrate(s) For Afmentioning
confidence: 99%
“…100 -103 This appears to be particularly true of the older athletic patient. The mechanisms producing atrial fibrillation in athletes are speculative, but a combination of exercise-induced left atrial remodeling and inflammation, 69,104 increased sympathetic activity during exercise, 100 and parasympathetically mediated slow resting heart rates potentiating atrial escape 93 has been suggested as a potential contributor.…”
Section: Arrhythmiamentioning
confidence: 99%